Multifactorial falls prevention programme compared with usual care in UK care homes for older people: multicentre cluster randomised controlled trial with economic evaluation. (7th December 2021) - Logan, Pip A; Horne, Jane C; Gladman, John R F; Gordon, Adam L; Sach, Tracey; Clark, Allan; Robinson, Katie; Armstrong, Sarah; Stirling, Sue; Leighton, Paul; Darby, Janet; Allen, Fran; et al.
Abstract: Objectives: To determine the clinical and cost effectiveness of a multifactorial fall prevention programme compared with usual care in long term care homes. Design: Multicentre, parallel, cluster randomised controlled trial. Setting: Long term care homes in the UK, registered to care for older people or those with dementia. Participants: 1657 consenting residents and 84 care homes. 39 were randomised to the intervention group and 45 were randomised to usual care. Interventions: Guide to Action for Care Homes (GtACH): a multifactorial fall prevention programme or usual care. Main outcome measures: Primary outcome measure was fall rate at 91-180 days after randomisation. The economic evaluation measured health related quality of life using quality adjusted life years (QALYs) derived from the five domain five level version of the EuroQoL index (EQ-5D-5L) or proxy version (EQ-5D-5L-P) and the Dementia Quality of Life utility measure (DEMQOL-U), which were self-completed by competent residents and by a care home staff member proxy (DEMQOL-P-U) for all residents (in case the ability to complete changed during the study) until 12 months after randomisation. Secondary outcome measures were falls at 1-90, 181-270, and 271-360 days after randomisation, Barthel index score, and the Physical Activity Measure-Residential Care Homes (PAM-RC) score at 91, 180, 270, and 360 days after randomisation. Results: Mean age of residents was 85 years. 32% were men. GtACH training was delivered to 1051/1480 staff (71%). Primary outcome data were available for 630 participants in the GtACH group and 712 in the usual care group. The unadjusted incidence rate ratio for falls between 91 and 180 days was 0.57 (95% confidence interval 0.45 to 0.71, P<0.001) in favour of the GtACH programme (GtACH: six falls/1000 residents v usual care: 10 falls/1000). Barthel activities of daily living indices and PAM-RC scores were similar between groups at all time points. The incremental cost was £108 (95% confidence interval −£271.06 to 487.58), incremental QALYs gained for EQ-5D-5L-P was 0.024 (95% confidence interval 0.004 to 0.044) and for DEMQOL-P-U was 0.005 (−0.019 to 0.03). The incremental costs per EQ-5D-5L-P and DEMQOL-P-U based QALY were £4544 and £20 889, respectively. Conclusions: The GtACH programme was associated with a reduction in fall rate and cost effectiveness, without a decrease in activity or increase in dependency. Trial registration: ISRCTN34353836 .